Heating rate and temperature effects on the BaTiO3 formation by thermal decomposition of (Ba,Ti) organic precursors during the Pechini process - Ramajo, L.; Parra, R.; Reboredo, M.; Zaghete, M. [UNESP]; Castro, M. (My University, 2008)
Different thermal treatments for the synthesis of BaTiO3 powder obtained through the Pechini method were studied. The synthesis of BaTiO3 starts at 150 °C by the thermal dehydration of organic precursors. The usual inevitable formation of barium carbonate during the thermal decomposition of the precursor could be retarded at lower calcination temperatures and optimized heating rates. The organic precursors were treated at temperatures between 200 and 400 °C. Then, the samples were calcined at 700 and 800 °C for 4 and 2 h, respectively. The resulting ceramic powders were characterized by gravimetric and differential thermal analyses, X-ray powder diffraction and infrared spectroscopy. It was found that depending on the heating rate and final temperature of the thermal treatment, high amounts of BaCO3 and TiO2 could be present due to the high concentration of organics in the final calcination step. © 2007 Elsevier B.V. All rights reserved.
Keywords: BaTiO3; Heat treatments; Infrared spectroscopy; Calcination; Heat treatment; Heating rate; Pyrolysis; Thermal effects; X ray powder diffraction; Organic precursors; Thermal dehydration; Barium titanate